Phage display technology in ecotoxicology: phage display derived unique peptide for copper identification in aquatic samples - Marta Sosnowska; Tomasz Łęga; Marcin Olszewski; Beata Gromadzka (Microbial Cell Factories)
Abstract Background Ecotoxicology is essential for the evaluation and comprehension of the effects of emergency pollutants (EP) such as heavy metal ions on the natural environment. EPs pose a substantial threat to the health of humans and the proper functioning of the global ecosystem. The primary concern is the exposure of humans and animals to heavy metal ions through contaminated water. The presence of heavy metal ions in drinking water ought to be monitored in accordance with World Health Organization regulations. Among the numerous harmful metal ions, copper ions are responsible for a variety of human diseases. Results This study investigates the application of phage display as a screening method for heavy metal toxicological targets, with copper served as the main focus. To identify a variety of Cu-binding M13 phage clones with unique peptides and to assess their affinity for metal ions, the study utilized Escherichia coli as a factories producing recombinant bacteriophages, modified biopanning procedure and an ELISA assay. The research highlights the increasing importance of phage display as a screening tool in ecotoxicology. We synthesized and modified the selected peptide to enable the rapid optical detection of Cu(II) ions in aqueous solutions. By incorporating the dansyl group into a designated peptide sequence, we implemented fluorescence detection assays for real-time measurements. The Cu2+- binding peptide’s efficacy was confirmed through spectroscopic measurements, which allowed for real-time detection with rapid response times with high selectivity. Conclusions The phage display technique was successfully applied to develop the fluorescent peptide-based chemosensor that exhibited high selectivity and sensitivity for Cu2+.